1998
DOI: 10.1002/(sici)1099-1395(199801)11:1<31::aid-poc968>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of allyl alcohol by alkaline periodate in the presence of micro amounts of palladium(II)

Abstract: The oxidation of allyl alcohol by alkaline species of periodate, H 2 IO 6 3À , was found to be catalysed by micro amounts of Pd(II) in 0.2 mol dm À3 alkali solution. The active species of the catalyst was found to be PdCl. A mechanism involving the interaction of the catalyst and substrate in prior equilibria leading to the formation of a pcomplex is proposed and the rate is derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…To further investigate such a conclusion, an in situ experiment was designed to explore further the chemical structure of PDA film. As already reported in the literature, the saturated KIO 4 can be used to oxidize alcohols into the corresponding carbonyls. In our case, we hypothesized that the PDA film obtained in Tris buffer consisting some OH groups, which is primarily expected for 5,6‐dihydroxyindoline and its derivative.…”
Section: Resultsmentioning
confidence: 81%
“…To further investigate such a conclusion, an in situ experiment was designed to explore further the chemical structure of PDA film. As already reported in the literature, the saturated KIO 4 can be used to oxidize alcohols into the corresponding carbonyls. In our case, we hypothesized that the PDA film obtained in Tris buffer consisting some OH groups, which is primarily expected for 5,6‐dihydroxyindoline and its derivative.…”
Section: Resultsmentioning
confidence: 81%
“…The data described above suggested to us that the as-prepared poly(dopamine) samples were composed primarily of noncovalent bonding interactions, including hydrogen bonding and charge transfer, as has been observed in other robust, synthetic or biological, supramolecular polymers and materials. To further support such a noncovalent model, poly(dopamine) powder was reacted with aqueous sodium hypochlorite (NaOCl, 5–6%) or potassium periodate (KIO 4 , saturated solution), both of which are commonly used for oxidizing alcohols to their corresponding carbonyls. We hypothesized that if poly(dopamine) was comprised of monomers bound by charge transfer, hydrogen bonding, or other supramolecular interactions (Figure ), oxidation of the mixture to the corresponding diones would be expected to degrade the polymer, allowing for analysis of small molecule products. Upon reaction with either of the aforementioned oxidants, the otherwise insoluble powder dissolved into the aqueous medium and transitioned from dark brown to clear and nearly colorless.…”
Section: Resultsmentioning
confidence: 97%
“…Its reactivity and biological effects are strongly influenced by the extent of it complexation with ligands . Pd (II) acts as a efficient catalyst in many redox reactions. It is also reported that Palladium-based catalysts are found to have high catalytic activity in clean deionized water. The literature survey shows that there is no report on the kinetics and mechanism of oxidation of tetracycline hydrate using Cu­(Bip) 2 2+ as oxidant and Pd­(II) chloride as homogeneous catalyst.…”
Section: Introductionmentioning
confidence: 99%